Response of Psoriasis with Systemic Lupus Erythematosus to Secukinumab: A Case Report and Review of the Literature - Dai B; Bai Y; Yu H; Huang Q; Wang L (Dove Medical Press, 2023)
Bowen Dai,1,2 Yanping Bai,2 HongDa Yu,1,2 Qiuchen Huang,1,2 Lei Wang2 1Graduate School, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 2Department of Dermatology and Venerology, China-Japan Friendship Hospital, Beijing, 100029, People's Republic of ChinaCorrespondence: Lei Wang, Department of Dermatology and Venereology, China-Japan Friendship Hospital, No. 2, Yinghua East Street, Chaoyang District, Beijing, 100029, People's Republic of China, Email wanglei010zyy@163.comAbstract: Although psoriasis and systemic lupus erythematosus are both immune abnormalities, there are few reports on Ps combined with SLE in China and abroad. We present a case of a 23-year-old female with a 10-year history of psoriasis, who had a relapse with significant joint symptoms and a PASI score of 35.6, along with several positive antibodies, including antinuclear antibodies, elevated CRP and ESR, and was diagnosed with psoriasis and SLE. She has been treated with secukinumab 300 mg subcutaneously, improving her condition. She is currently being followed up. The PubMed, SCOPUS, and ISI Web of Science databases were thoroughly searched for English studies reporting psoriasis with systemic lupus erythematosus and treated using biologics. Three case reports/series were included after the screening. Our case report provides a reference for clinicians using secukinumab to treat psoriasis combined with SLE. However, further research is needed to determine whether it can be widely used or if there are common signaling pathways that can be interfered with the pathogenesis of the diseases.Keywords: psoriasis, systemic lupus erythematosus, secukinumab